On ma- Separation Axiom In Biminimal Space - kadhim, Hussein (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper deals with the extension and development of some of the concepts of the separation axiom in topological space into biminimal spaces. In Addition, to give new results and theorems, supported by illustrative examples.